Features distribution of dynamic perturbations in an elastic multisuppot construction - Ashirbayev, N.K.; Ashirbayeva, Zh.N.; Altynbekov, Sh.E.; Shomanbayeva M.Т. (Bulletin of the Karaganda University. Mathematics Series, 2016)
The article discusses the problem of propagation of dynamic perturbations in an elastic multibasic design is a rectangular strip. Formulated in terms of the stress and velocity mixed problem is simulated numerically using the explicit diﬀerence scheme through calculation based on the method of spatial characteristics. The main objective of this study is to analyze the impact of the gap in the boundary conditions on the distribution of wave processes in the interior of the study of the elastic medium. We consider the dynamic stress concentration in the vicinity of the gap boundary conditions.